Effect of local injection of injectable platelet-rich fibrin on eruption rate of teeth (Rabbit animal model) - Enas Talb Al-Jwary; Niam Riyadh Al-Saleem (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVE: This study aimed to evaluate the effect of the local injection of injectable platelet-rich fibrin (i-PRF) on the eruption rate of the teeth and evaluation of the effect of i-PRF on the number of odontoblast, cementoblast, osteoblast, osteocyte, and osteoclast cells. MATERIALS AND METHODS: The samples consisted of 20 male albino rabbits and were divided randomly into the control group (5 rabbits) and i-PRF groups (15 rabbits) sub-divided into week 1, week 2, and week 3 sub-groups. The labial surface of lower right incisors was marked by drilling a hole at the level of the free gingival margin in the mid-line of each tooth with a small round bur, and the eruption rates were measured by measuring the distance from the most apical point of the free gingival margin and the center of the hole with a digital caliper. i-PRF was prepared by centrifuging autologous blood of each rabbit at 1000 rpm for 5 minutes; then the i-PRF layer was collected. The control group received no treatment, whereas i-PRF groups received i-PRF in the following manner: For week 1 groups, a single dose was given at 0 day; for week 2 groups, double doses were given at 0 and 7 days; and for week 3 groups, three doses were given at 0, 7, and 14 days. At the end of experiments for each group, animal scarification was performed, and histological steps were performed. RESULTS: There was a significant increase in the rate of tooth eruption in i-PRF groups when compared to the control group, and the eruption rate was increased in 107.3%, 144.7%, and 167.5% for week 1, week 2, and week 3, respectively. Concerning the histological finding, the i-PRF groups gave rise to a higher number of odontoblast, cementoblast, osteoblast, osteocyte, and osteoclast cells with a significant difference when compared to the control groups (P ≤ 0.05). CONCLUSIONS: Applying i-PRF significantly increased the rate of teeth eruption at all-time intervals. Platelet-rich fibrin injection can be an effective method for acceleration of teeth eruption.